Notes on the Fo yi jing 佛醫經 T793 - Lin, Qian; Radich, Michael (JAOS, 2023)
The Fo yi jing 佛醫經 T793, a short text, discusses physical and mental health, presenting its content as the teachings of the Buddha. The Taishō presents the text as translated by Zhu Lüyan 竺律炎 and Zhi Qian 支謙 . We survey bibliographic records to propose that this attribution is unreliable. Using computer assisted analysis, we locate passages in the text possibly borrowed from early Chinese sources, among them most notably An Shigao’s 安世高 Jiu heng jing 九橫經 T150A(31) . These findings indicate that T793 was probably compiled in China on the basis of various sources. We also find that some basic early Buddhist teachings, such as the four nutriments (āhāra) and rules regarding the eating of meat, are misunderstood or misrepresented in T793 . Taking into account some terms and phrases in T793 that occur more frequently in translations in the Western Jin period, we suggest that T793 is likely a compilation made between the late third and early fourth centuries. It is thus probably one of the earliest extant Chinese compositions of this kind.
Gesehen am 03.12.2025